Clamp links: A novel type of reciprocal frame connection. (June 2022) - Castriotto, Caio; Tavares, Felipe; Celani, Gabriela; Popovic Larsen, Olga; Browne, Xan
Reciprocal frames (RFs) are complex structural systems based on mutual support between elements. One of the main challenges for these structures is achieving geometrical complexity with ease for assembly. This paper describes the development of a new type of connection for RF that uses a single bolt to fix a whole fan. The method used was the Research Through Design, using algorithmic modelling and virtual and physical prototyping. After the exploration of different alternatives, the connection selected was structurally evaluated with a 3D solid finite element analysis (FEM) software and a 2D bar parametric model. Finally, a full-scale pavilion was built as a proof-of-concept. A total of 47 connections were fabricated using four 3D-printed templates combined with a hand router. The construction allowed us to draw conclusions on the connection design and the assembly method, and the process as a whole can contribute to the development of new structural links and production methods.